Vitamin D Deficiency in Children With Vasovagal Syncope Is Associated With Impaired Circadian Rhythm of Blood Pressure - Zou, Runmei; Wang, Shuo; Cai, Hong; Li, Fang; Lin, Ping; Wang, Yuwen; Wang, Cheng (Frontiers in Neuroscience, 2021)
Background Vitamin D deficiency is associated with the risk of cardiovascular diseases. We aimed to investigate the serum vitamin D levels in children with vasovagal syncope (VVS) and explore the correlation of vitamin D status and circadian rhythm of blood pressure in VVS pediatric patients. Methods This was a retrospective study. 130 syncopal children diagnosed with VVS were included in the study. 110 age and gender matched healthy individuals were enrolled as control. According to serum 25(OH)D levels, VVS patients were divided into vitamin D sufficient group and vitamin D deficient group. Detailed information of VVS children with vitamin D deficiency and sufficiency on demographic data, baseline laboratory testing, echocardiogram, ambulatory blood pressure monitoring, and Holter ECG recording were extracted and analyzed. Results VVS children had a higher prevalence of vitamin D deficiency compared with healthy individuals (33.8% vs. 20.0%, P = 0.017). VVS patients with vitamin D deficiency had a higher rate of non-dipper blood pressure (79.5% vs. 59.3%, P = 0.021) and a lower value of square root of mean squared differences of successive normal to normal intervals (rMSSD) (median 107.8 vs. 141.0 ms, P = 0.035) compared with those with vitamin D sufficiency. Logistic regression analysis showed that non-dipper blood pressure was associated with serum 25(OH)D level [OR = 0.979, 95% CI (0.960, 0.999), P = 0.036]. Conclusion VVS pediatric patients had a higher prevalence of vitamin D deficiency. VVS children with vitamin D deficiency showed a higher rate of non-dipper blood pressure, suggesting that vitamin D deficiency is correlated with impaired circadian rhythm of blood pressure.